674.DESIGN, ANALYSIS, AND OPTIMIZATION OF THE STEERING COLUMN SYSTEM FOR AN ELECTRIC STREET SWEEPER - Elena, Angeleska; Vasko, Čangoski; Blagoja, Nestorovski; Anita, Vasileva (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2024)
This study explores the challenges and solutions related to improving the interior ergonomics of a small street sweeper, with a specific focus on redesigning the steering column and brake pedal system. The initial design faces issues such as obstructed field of view and limited space in the operator's knee area. The primary objective is to enhance comfort and safety for the operator within the constraints of the existing design. The proposed solution involves a new steering column structure that integrates the brake pedal system. Siemens Jack software was employed for ergonomic analysis, revealing improved operator comfort and larger field of view with the modified design. Dy-namic analysis using ADAMS View confirmed that the new brake pedal system met the requirements outlined in the ECE R13 regulation. This solution improves ergonomics, offers larger field of view, and ensures optimal brake perfor-mance.